ANALISA PENGARUH KEDALAMAN POTONG DAN KECEPATAN POTONG TERHADAP KERATAAN PERMUKAAN BAJA AISI 1045 PADA MESIN BUBUT CNC - Sulistyono, Djoko; Anif, Muhammad Nur (MEKANIKA: Jurnal Teknik Mesin, 2017)
One of the components or parts that are required to have a low surface roughness, namely the shaft. Thus in line with these developments are also components (shaft) or parts produced in CNC lathe machining processes must have a good level of surface roughness. This study aims to determine the effect of depth of cut and cutting speed in the process of material AISI perautan in 1045. The experimental design used is variasi speed cutting with a depth of cut of each tested three times objects. From the analysis of the cutting speed and depth of cut affects the surface flatness surface cutting results where (Ra) is the lowest. In the AISI 1045 material obtained to cutting with cutting speed 93 m/min with a cutting depth of cut 0.1 mm average price obtained for the surface flatness is 1.16 µm. For the depth of cut 0.2 mm average price obtained for the surface flatness is 1.21 µm. For the depth of cut 0.3 mm average price obtained for the surface flatness is 1.31 µm. To cutting with cutting speed 79 m/min with a cutting depth of cut 0.1 mm average price obtained for the surface flatness is 1.23 µm. For the depth of cut 0.2 mm average price obtained for the surface flatness is 1.27 µm. For the depth of cut 0.3 mm average price obtained for the surface flatness is 1.32 µm. To cutting with cutting speed 79 m/min with a cutting depth of cut 0.1 mm average price obtained for the surface flatness is 1.25 µm. For the depth of cut 0.2 mm average price obtained for the surface flatness is 1.28 µm. For the depth of cut 0.3 mm average price obtained for the surface flatness is 1.35 µmKeywords: AISI 1045, Cut Speed, Ingestion thickness, surface flatness